Relationships between Personal Traits, Emotional Intelligence, Internal Marketing, Service Management, and Customer Orientation in Korean Outpatient Department Nurses - Bogyun Kim, MSN, RN; Jia Lee, PhD, RN (Elsevier, 2016)
Purpose: Current increase and complexity of medical tests and surgical procedures at outpatient department (OPD) require OPD nurses to have customer orientation focusing on various customers' interests and needs. The purpose of this study was to identify the factors associated with customer orientation in nurses working at OPD of hospitals. Methods: The study used a descriptive correlational design with cross-sectional survey. The study settings were four general hospitals in Seoul and its metropolitan area. Data were collected from 138 OPD nurses from general hospitals. Study variables were personal traits, emotional intelligence, internal marketing, service management and customer orientation. Results: Factors associated with customer orientation were identified as conscientiousness from personal traits (β = .37, p < .001), emotional intelligence from individual characteristics (β = .21, p = .032), and internal marketing from environmental characteristics (β = .21, p = .001). Conclusions: Hospital administrators should support OPD nurses to cultivate sincere and sociable personal traits and emotional intelligence, and to consider employees as internal customers to improve patient-oriented services and satisfaction.